POLITICIZATION OF RELIGION: The Quran as a Commodity of Religious Texts in Indonesia - Said, Hasani Ahmad; Tsauri, M. Najib (Ulul Albab: Jurnal Studi Islam, 2025)
This article examines the politicization of religion in Indonesia, with a focus on the Quran’s transformation into a political and social commodity. Through a qualitative case study conducted in Jakarta and West Java, involving 42 informants from various sectors, including religious, political, academic, and community, the study revealed that sacred texts are frequently decontextualized and manipulated to legitimize political agendas. The Quran’s instrumentalization has intensified social polarization, undermined theological integrity, and weakened public trust in both religious institutions and democratic processes. The analysis identifies four main typologies of manipulation: political delegitimization, instrumental legitimacy, explicit desecration, and commodification within the digital and commercial sphere. Using the maqâs{id al-sharîah framework, these practices obviously violate fundamental Islamic objectives—particularly h{ifz{ al-dîn, h{ifz{ al-aql, and h{ifz{ al-nasl. However, three Indonesian cultural values (cooperation, communal harmony, and peaceful coexistence) offer cultural resilience countering these tendencies through inclusive education and critical religious literacy. The study concludes that genuine religiosity must be rooted in the Quran’s ethical application rather than its political instrumentalization. Restoring the Quran's sanctity requires a synthesis of scriptural fidelity, civic responsibility, and cultural wisdom to ensure religion functions as a unifying moral force rather than a divisive political tool. This study offers two key contributions. Theoretically, it introduces a comprehensive framework for interpreting the Quran as both a sacred text and a politicized social commodity. Practically, it presents evidence-based strategies to help policymakers, religious authorities, and civil society mitigate religious politicization while promoting theological integrity and social unity within Indonesia’s pluralistic democracy.